Structure, Vibrational Analysis and Chemical Reactivity Descriptors of 4-Bromo-3-(Methoxymethoxy) Benzoic Acid: A DFT Study - Yadav, S.; Khare, A.; Yadav, K. K.; Maurya, P. C.; Singh, A. K.; Kumar, A. (Journal of Scientific Research, 2022)
In this study, the structure and various molecular parameters of 4-bromo-3-(methoxymethoxy) benzoic acid are determined at the B3LYP/6-311++G(d,p) level of theory. Present study provides comparision and discussion of calculated and experimental optimized parameters. The values of descriptors such as ionization energy, hardness, electrophilicity, condensed Fukui function and energy were determined to predict the reactivity of 4-bromo-3-(methoxymethoxy) benzoic acid. The influence of the solvent on reactivity parameters has been studied adopting the PCM model. The analysis shows that solvation alters the values of reactivity descriptors. A vibrational assessment of the molecule has also been performed. To gain a better understanding of the properties of the title molecule, parameters such as the molecular electrostatic potential surface and the HOMO-LUMO band gap have been computed. The dipole moment, polarizability and hyperpolarizability were also estimated to probe into non-linear optical properties of the chemical.